2004
DOI: 10.1109/tnb.2004.833680
|View full text |Cite
|
Sign up to set email alerts
|

Agent-Based Computational Modeling of Wounded Epithelial Cell Monolayers

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 20 publications
1
109
0
1
Order By: Relevance
“…Indeed, a C-ImmSim model captures important elements of EBV infection [46]. Other studies using agent-based simulation to address the course of specific diseases include [47][48][49][50][51][52][53][54].…”
Section: It Is Very Much An Open Question As To What Sort Of Mathematmentioning
confidence: 99%
“…Indeed, a C-ImmSim model captures important elements of EBV infection [46]. Other studies using agent-based simulation to address the course of specific diseases include [47][48][49][50][51][52][53][54].…”
Section: It Is Very Much An Open Question As To What Sort Of Mathematmentioning
confidence: 99%
“…The central scratch has been used with multiple cell types and, as the monolayers heal the wound in a characteristic manner, they have been used to study cell polarization, matrix remodeling, cell migration, and numerous other processes [12]. Kornyei et al (2000) [14] used an in vitro scratch-wound model to investigate astroglial responses to mechanical injury while Saga et al (2003) [15], Liang et al (2004) [16], Farooqui et al (2004) [17], and Walker et al (2004) [18] used the cell scratch-wound model to study the proliferative and migratory responses of different cells. Lau et al (2001) [19] focused on the production of four inflammatory cytokines in primary culture using an injury model which simulated in vivo mechanical trauma and reported that all four cytokines began to increase 1 hour post-scratch and remained at high levels throughout the experiment [19].…”
Section: Introductionmentioning
confidence: 99%
“…ABMs have been successfully applied to problems similar to that discussed here, which are defined in figure 5 (57,58). It is appropriate to conclude this section by highlighting one final advantage of our multi-scale methodology.…”
Section: Multi-scale Multi-physics Modelingmentioning
confidence: 92%